DETERMINAN PENGGUNAAN PINJAMAN ONLINE SYARIAH DI INDONESIA - Widya, Eka Arista; Pimada, Laila Masruro (Islamic Economics and finance in Focus, 2023)
Based on Fintech Lending Statistical data 2020 – 2022 published by Otoritas Jasa Keuangan, the growth value of sharia online loans in Indonesia is still far behind compared to conventional online loans. However, when viewed from a consumer protection perspective, Islamic online loans have many advantages over conventional online loans. The advantages in terms of consumer protection can be an opportunity for the development of Islamic online loans in Indonesia, so that research on the factors that influence people to use Islamic online loans is important to study. This study aims to identify what factors influence the use of Islamic online loans in Indonesia. As for this research, it is only focused on sharia online loans, where loan funds are used for consumptive activities. This research is quantitative research. There are 100 samples of respondents who are at least 17 years old with the condition that they have used or applied for funds on an online sharia loan with the aim of fulfilling consumption at least once. By using SPSS software, method applied is factor analysis. Research shows that the use of sharia online loans in Indonesia is influenced by Islamic Financial Literacy factors, Debt Perception factors and Risk Perception factors.